Modeling Emotional Valence Integration From Voice and Touch - Tsalamlal, Yacine; Amorim, Michel-Ange; Martin, Jean-Claude; Ammi, Mehdi (Frontiers in Psychology, 2018)
In the context of designing multimodal social interactions for Human–Computer Interaction and for Computer-Mediated Communication, we conducted an experimental study to investigate how participants combine voice expressions with tactile stimulation to evaluate emotional valence. In this study, audio and tactile stimuli were presented separately, and then presented together. Audio stimuli comprised positive and negative voice expressions, and tactile stimuli consisted of different levels of air jet tactile stimulation performed on the arm of the participants. Participants were asked to evaluate communicated emotional valence on a continuous scale. Information Integration Theory was used to model multimodal valence perception process. Analyses showed that participants generally integrated both sources of information to evaluate emotional valence. The main integration rule was averaging rule. The predominance of a modality over the other modality was specific to each individual.